O casal Gilchrist e a vida de um pintor desconhecido: o gênero biografia e a recepção da obra de William Blake no século 19 - Canto, Daniela Schwarcke do (2015)
This study has as main objective to analyze the biography of William Blake: dreamed and researched by Alexander Gilchrist and finished by his wife Anne Gilchrist and by the painter and writer Dante Gabriel Rossetti. Considered a mad genius that talked to spirits by a great part of his contemporaries, William Blake became known only after his death, in 1827, for his works as a poet, painter and engraver. In a first moment, a short biography of Alexander Gilchristis presented, as well as of the others involved in the writing of the biography Life of William Blake: Pictor Ignotus. In the second chapter, an analysis is conducted on what Gilchrist wrote about Blake s technical side and his educational background. The third chapter is about the visionary Blake, and how these episodes are portrayed in the Gilchrist s biography. In the last chapter, a parallelis traced between what Alexander Gilchrist wrote in his biography and what five authors before him wrote on Blake. These authors are: Cunningham, J. T. Smith, Malkin, Tatham and Crabb Robinson. In this way, we intend to reach a hypothesis on which authors were used as sources by Gilchrist to write Life of William Blake: Pictor Ignotus.